Formation of the gas flow in the plasma-chemical reactor - Vyacheslav Fedorovich Myshkin (Mishkin); Valery Alekseevich Khan; Evgeniy Vladimirovich Bespala; Milan Tichy; Dmitry Aleksandrovich Izhoykin (Известия Томского политехнического университета: Инжиниринг георесурсов, 2017)
The relevance of the discussed issue is caused by the need to optimize the geometry of the plasma-chemical reactor to increase the isotope effects. The main aim of the study is the search for the optimal geometry of plasma-chemical reactor, which provides high-localization of the plasma flow in the axial region for increasing isotope effects by reducing the back diffusion effect, leading to equalization of isotope concentration. The methods used in the study: calculation and optimization of the gas flow within the plasma-chemical reactor by the unsteady Navier? Stokes equations and Fourier by the method of finite-difference components using ANSYS Fluent. The results. The authors explained the mechanism of isotopic concentration change in the products of plasma-chemical reactions due to the spin separation of carbon isotopes in a nonequilibrium low-temperature plasma in a magnetic field. An analysis of the processes occurring inside the plasma-chemical reactor of constant width was carried out. It is expected that the reduction of isotope effects is associated with the oxidation of the dispersed phase, which is located on the reactor walls. A method and apparatus for limiting the contact area of the high-temperature plasma flow with the walls of the chamber was proposed. Calculation of gas flows inside the plasma-chemical reactor of the selected geometry was carried out. It is shown that for the contraction of high temperature gas flow in the central region and isolating it from the walls of the plasma reactor can be used thin diaphragm of temperature-resistant material. It was also shown that the wall temperature of the plasma-chemical reactor in the region between the diaphragms does not exceed the evaporation temperature of the dispersed phase in some plasma gas flow. The highest possible isotope effect which occurs in the processes of plasma in a magnetic field is largely retained.